Polymer-mediated nanorod self-assembly predicted by dissipative particle dynamics simulations - Khani, Shaghayegh; Jamali, Safa; Boromand, Arman; Hore, Michael J. A; Maia, Joao (Soft matter, 2015)
Self-assembly of nanoparticles in polymer matrices is an interesting and growing subject in the field of nanoscience and technology. We report herein on modelling studies of the self-assembly and phase behavior of nanorods in a homopolymer matrix, with the specific goal of evaluating the role of deterministic entropic and enthalpic factors that control the aggregation/dispersion in such systems. Grafting polymer brushes from the nanorods is one approach to control/impact their self-assembly capabilities within a polymer matrix. From an energetic point of view, miscible interactions between the brush and the matrix are required for achieving a better dispersibility; however, grafting density and brush length are the two important parameters in dictating the morphology. Unlike in previous computational studies, the present Dissipative Particle Dynamics (DPD) simulation framework is able to both predict dispersion or aggregation of nanorods and determine the self-assembled structure, allowing for the determination of a phase diagram, which takes all of these factors into account. Three types of morphologies are predicted: dispersion, aggregation and partial aggregation. Moreover, favorable enthalpic interactions between the brush and the matrix are found to be essential for expanding the window for achieving a well-dispersed morphology. A three-dimensional phase diagram is mapped on which all the afore-mentioned parameters are taken into account. Additionally, in the case of immiscibility between brushes and the matrix, simulations predict the formation of some new and tunable structures. Three dimensional phase diagram for controlled aggregation/dispersion of polymer grafted nano-rods in a polymer matrix.